Reaction of selected carbohydrate aldehydes with benzylmagnesium halides: benzyl versus o-tolyl rearrangement - Bella, Maroš; Steiner, Bohumil; Langer, Vratislav; Koóš, Miroslav (Beilstein Journal of Organic Chemistry, 2014)
The Grignard reaction of 2,3-O-isopropylidene-α-D-lyxo-pentodialdo-1,4-furanoside and benzylmagnesium chloride (or bromide) afforded a non-separable mixture of diastereomeric benzyl carbinols and diastereomeric o-tolyl carbinols. The latter resulted from an unexpected benzyl to o-tolyl rearrangement. The proportion of benzyl versus o-tolyl derivatives depended on the reaction conditions. Benzylmagnesium chloride afforded predominantly o-tolyl carbinols while the application of benzylmagnesium bromide led preferably to the o-tolyl carbinols only when used in excess or at higher temperatures. The structures of the benzyl and o-tolyl derivatives were confirmed unambiguously by NMR spectral data and X-ray crystallographic analysis of their 5-ketone analogues obtained by oxidation of the corresponding mixture of diastereomeric carbinols. A possible mechanism for the Grignard reaction leading to the benzyl→o-tolyl rearrangement is also proposed.
Keywords: aldehyde; benzyl versus o-tolyl; carbohydrate; Grignard reaction; rearrangement; X-ray crystallography